Unravelling groundwater contributions to evapotranspiration and constraining water fluxes in a high‐elevation catchment. Issue 1 (4th January 2022) - Ryken, Anna C.; Gochis, David; Maxwell, Reed M.
Abstract: Despite the importance of headwater catchments for the water supply of the western United States, these regions are often poorly understood, particularly with respect to quantitative understanding of evapotranspiration (ET) fluxes. Heterogeneity of land cover, physiography, and atmospheric patterns in these high‐elevation regions lead to difficulty in developing spatially‐distributed characterization of ET. As the largest terrestrial water flux behind precipitation, ET represents a significant fraction of the water budget for any watershed. Likewise, groundwater is the largest available freshwater store and has been shown to play a large role in the water balance, even in headwater systems. Using an eddy covariance tower in the East River Catchment, a Colorado River headwaters basin, we estimated water and energy fluxes in high‐elevation, complex systems to better constrain ET estimates and calculate overall water and energy budgets, including losses from groundwater. We used the eddy covariance method to estimate ET from years 2017 through 2019 at a saturated, riparian end‐member site. Owing to complexities in near surface atmospheric structure such as stable boundary layers over snowpack and shallow terrain driven flow from surrounding landscape features, energy flux and ET estimates were limited to the warm season when energy closure residuals from the eddy‐covariance system were reliably less than 30%, a threshold commonly used in eddy covariance energy flux estimation. The resulting ET estimations are useful for constraining water budget estimates at this energy‐limited site, which uses groundwater for up to 84% of ET in the summer months. We also compared East River ET magnitudes and seasonality to two other flux towers (Niwot Ridge, CO and Valles Caldera, NM), located in the Rocky Mountains. These data are useful for constraining ET estimates in similar end‐member locations across the East River Catchment. Our results show that groundwater‐fed ET is a significant component of the water balance and groundwater may supply riparian ET even during low‐snow years. Abstract : Estimates of evapotranspiration from an eddy covariance tower in the East River watershed are useful for constraining both the energy and water budgets in mountain headwater basins. These ET estimates are useful for calculating the water balance of the catchment as well as estimating the amount of groundwater contributing to ET.